Identification of Potential Regulatory Genes Associated with Chondrosarcoma using Integrated Bioinformatic Analysis - Mohamad Dimas Ismail; Firman Hasan; Wijaya Johanes Chendra (Indonesian Journal of Global Health Research, 2023)
Identifying the novel critical regulatory genes in the molecular processes driving chondrosarcoma (CS) growth is essential for establishing targeted therapeutic approaches. Objective: This study aims to investigate the core regulatory genes implicated in the molecular mechanisms of CS progression. Method: We conducted a dataset search from the Gene Expression Omnibus (GEO) database using “chondrosarcoma” as the keyword. DAVID database was utilised to obtain the Gene Ontology (GO) and pathways enrichment of DEGs. Interaction between the proteins network was constructed using the STRING database and visualised by Cytoscape (3.10.0) software. Subsequently, the essential genes were identified as the intersected genes from cytoHubb and MCODE plugin. Furthermore, we analysed these genes based on their expression and survival using the UALCAN database. Additionally, the cBioPortal database and Tumor Immune Estimation Resource (TIMER) were utilised to obtain the genetic alteration and immune cell infiltration associated with the hub genes. Moreover, the NetworkAnalyst database was deployed to construct the interactions between microRNAs (miRNAs) and the hub genes. Results: 114 common DEGs were found between two datasets (GSE30844 and GSE48418). These genes are predominantly associated with Focal Adhesion. Seven hub genes were identified which include CCND1, CDK6, CAV1, MLC1, SQSTM1, GAPDH, and FOXO1. The validation analysis revealed a diagnostic value amidst the hub genes, particularly CDK6 and FOXO1 genes associated with unfavorable outcome in sarcoma patients. The miRNAs analysis demonstrated that miR-15a-5p has a potential binding with CDK6 and FOXO1. Conclusions: This study revealed seven core genes and indicated a putative regulatory molecule associated with CS progression. Taken together, this study's findings suggest that the CDK6, FOXO1, and miR-15a-5p have a potential role in regulating CS progression.